Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
By using doped iron manganese phosphate core and lithium-containing carbon clad structure in the lithium-ferrophosphate positive electrode material, the problem of rapid attenuation of the voltage platform during the battery cycle is solved, and the cyclic stability and conductive properties of the material are significantly improved.
Patent Information
- Application Number
- CN202411843248.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
The lithium manganese iron phosphate positive electrode material has the problem of rapid attenuation under the 4.1V voltage platform during the battery cycle, resulting in poor circulation performance and serious capacity attenuation.
The doped iron manganese phosphate core and lithium-containing carbon clad structure are adopted, and the doped ion gradient distribution is distributed, the content of manganese ions and iron ions decreases from the inside to the outside, and the content of doped ions increases from the inside to the outside.
It effectively improves the phase structure stability and conductivity of lithium manganese iron phosphate positive electrode material, reduces manganese dissolution phenomenon and Jahn-Teller effect, and improves the cyclic stability and capacity retention rate of the material.
Smart Images

Figure CN119725439A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium batteries, and in particular to a lithium iron manganese phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium iron phosphate cathode material not only has the advantages of high energy density and long cycle life, but also has the advantages of high safety and no memory effect. In recent years, lithium iron phosphate cathode material has been applied to the field of power batteries and energy storage. However, due to its low voltage platform (3.4V relative to Li / Li + ), low stacking density, and low rate performance restrict the wider application of lithium iron phosphate positive electrode materials.
[0003] Lithium manganese iron phosphate material is a positive electrode material obtained by compounding manganese elements on the basis of lithium iron phosphate. It has a higher discharge platform (3.5~4.1V relative to Li / Li + ), so that the overall theoretical energy density of the material can be increased by about 21% compared with that of lithium iron phosphate material. However, when lithium iron manganese phosphate is used in battery cycling, there is a problem of rapid decay of the 4.1V platform. The main reasons for the above problems are as follows: ① The phase structure stability of the material itself is not high and the microscopic morphology is irregular; ② The lithium iron manganese phosphate material itself will have the Jahn-Teller effect; ③ Manganese will dissolve in the lithium iron manganese phosphate material; ④ The lithium iron manganese phosphate material has poor lithium ion conductivity. There are many methods for preparing lithium iron manganese phosphate materials, which are listed as follows:
[0004] CN102249208A discloses a method for preparing a positive electrode material of a lithium manganese iron phosphate battery by a hydrothermal method. The method firstly prepares LiMn by a hydrothermal synthesis reaction. x Fe 1-x PO4: Stir and mix lithium hydroxide aqueous solution, ferrous sulfate aqueous solution and phosphoric acid, raise the temperature to 150-180°C within 0.5-2.0 hours under sealed conditions, react for 0.5-4 hours under a pressure of 0.48-1.0 MPa, cool to below 80°C, and filter; then mix the filtered product wet cake with soluble carbon source organic matter, spray dry or flash dry; finally, LiMn x Fe 1-x The PO4 carbon source composite powder is calcined at 600-750°C for 4-6 hours under inert gas conditions and cooled to below 150°C to obtain a carbon-coated lithium manganese iron phosphate lithium ion battery positive electrode material.
[0005] CN103000898A discloses a method for preparing a carbon composite manganese iron lithium phosphate material. The method allows the raw materials to be uniformly mixed at the molecular level, which is conducive to obtaining a homogeneous precursor. The method mainly includes two parts. First, the manganese source and the phosphorus source are dissolved to form an aqueous solution, and anhydrous ethanol is dripped into the aqueous solution. When the system produces a precipitate, it is stirred, filtered, washed, and dried to obtain a precursor; second, the precursor is ball-milled with a lithium source and a ferrous salt, and dried to form a mixture, and then calcined and cooled to obtain a carbon composite manganese iron lithium phosphate material.
[0006] CN102969506A discloses a modified lithium iron manganese phosphate positive electrode material and a preparation method thereof. The specific preparation process disclosed in the invention is as follows: (1) placing a phosphorus source, an iron source and a manganese source in a reactor and stirring the reaction at a speed of 800 to 1500 r / min, and heating to 60 to 100°C for reaction for 5 to 18 hours. After the reaction is completed, the mixture is dried and crushed; (2) pre-calcining: under nitrogen protection, heating to 500 to 700°C at a speed of 2 to 10°C / min and keeping warm for 5 to 10 hours, and then cooling with the furnace; (3) mixing: mixing the pre-calcined product with a certain amount of lithium source, adding a carbon source, using anhydrous ethanol as a dispersant, and ball milling at 800 to 2000 r / min on a ball mill for 2 to 10 hours. After ball milling, the product is dried and crushed; (4) high-temperature sintering: under nitrogen protection, heating to 600 to 900°C at a speed of 2 to 10°C / min and keeping warm for 5 to 20 hours, and then cooling with the furnace to obtain a lithium iron manganese phosphate positive electrode material.
[0007] CN102738465A discloses a method for preparing lithium iron manganese phosphate material by solid phase method, wherein a lithium source, a trivalent iron source, manganese dioxide, a phosphorus source and a carbon source are put into a ball mill, a dispersant and a complexing agent are added and mixed, and then ball milled on a ball mill, and then dried and sintered to prepare LiMn x Fe 1-x PO4 positive electrode material.
[0008] CN115321507A discloses a method for preparing lithium manganese iron phosphate material by coprecipitation, in which a mixed solution of manganese source, iron source, phosphoric acid and perchloric acid is added to an alkaline solution for coprecipitation reaction, and finally the coprecipitation product is washed and dried to obtain a positive electrode material of manganese iron phosphate. The manganese source and iron source used in the preparation method are both cyanide, which is harmful to the environment and difficult to achieve large-scale production and application.
[0009] The lithium iron manganese phosphate positive electrode materials prepared in the above-mentioned method for preparing the lithium iron manganese phosphate positive electrode material all have defects to a certain extent. In order to specifically improve a series of problems caused by defects such as poor phase structure stability, irregular micromorphology, poor conductivity, and Jahn-Teller effect and manganese dissolution of the lithium iron manganese phosphate positive electrode material itself, the present invention is specially proposed. Summary of the invention
[0010] The main purpose of the present invention is to provide a lithium iron manganese phosphate positive electrode material and a preparation method and application thereof, so as to solve the problems of the lithium iron manganese phosphate material in the prior art, such as poor phase structure stability, poor lithium ion conductivity, Jahn-Teller effect and manganese dissolution in the material itself, which lead to poor cycle performance and severe capacity decay of the lithium iron manganese phosphate positive electrode material during application in batteries.
[0011] In order to solve the above problems, the present invention provides a lithium iron manganese phosphate positive electrode material, which includes a doped manganese iron phosphate core and a coating layer coated on the surface of the doped manganese iron phosphate core, wherein the coating layer is a lithium-containing carbon layer; the doped manganese iron phosphate core includes doped ions, and the particles of the doped manganese iron phosphate core have a decreasing content gradient of manganese ions and iron ions from the inside to the outside, and an increasing content gradient of doped ions. The lithium iron manganese phosphate positive electrode material can effectively improve the manganese dissolution phenomenon existing in the lithium iron manganese phosphate material during use, and can further improve the cyclability and serious capacity attenuation of the lithium iron manganese phosphate positive electrode material, and can further improve the conductivity of the lithium iron manganese phosphate positive electrode material and improve the comprehensive performance of the material.
[0012] Furthermore, the chemical formula of the lithium manganese iron phosphate positive electrode material is: LiFe 1-x-y Mn x M y PO4 / C, wherein 0.1≤x≤0.9, 0.002≤y≤0.02, and M is one or more of nickel, cobalt, magnesium, titanium, copper, vanadium, zirconium and chromium; preferably, LiFe 1-x- y Mn x M y In PO4 / C, 0.5≤x≤0.7, 0.01≤y≤0.02; preferably, the particle size of the lithium manganese iron phosphate positive electrode material is 0.5-10 μm; preferably, the carbon coating amount of the coating layer is 1%-3%; preferably, M is cobalt and / or magnesium. Controlling the component content of the lithium manganese iron phosphate positive electrode material within the above range is more effective in improving the comprehensive performance of the material.
[0013] According to another aspect of the present invention, a preparation method of the above-mentioned lithium iron manganese phosphate positive electrode material is also provided, and the preparation method comprises the following steps: S1, dissolving a manganese source and an iron source in water to obtain a manganese iron mixed solution; dissolving a soluble compound of doping ions in water to obtain a doping ion solution; S2, placing a complexing agent aqueous solution in a reaction vessel, and adding phosphoric acid to adjust the pH; S3, adding the manganese iron mixed solution and the doping ion solution to the reaction vessel in a co-current dropwise manner to carry out a co-precipitation crystallization reaction to obtain a crystalline precipitate; in the co-current dropwise process, controlling the flow rate of the doping ion solution to gradually increase; S4, filtering, washing and drying the crystalline precipitate to obtain a gradient doped iron manganese phosphate precursor; S5, mixing the iron manganese precursor with a lithium source, a carbon source and water to obtain a mixed slurry, and grinding, spray drying, sintering and crushing the mixed slurry to obtain a lithium iron manganese phosphate positive electrode material. Using the above-mentioned preparation method, the performance of the obtained lithium iron manganese phosphate positive electrode material is better.
[0014] Furthermore, in step S1, the concentration of the manganese iron mixed solution is 0.8-1.2 mol / L; preferably, the concentration of the doping ion solution is 0.3-0.6 mol / L. Controlling the concentration of the manganese iron mixed solution and the concentration of the doping ion solution within the above range is conducive to improving the comprehensive performance of the lithium manganese iron phosphate positive electrode material.
[0015] Further, the co-current addition operation is carried out under stirring, and the addition rate of the manganese iron mixed solution is 0.5-5L / h; preferably, the initial addition rate of the doping ion solution is 0.005-0.5L / h, and when the crystal size reaches 3-5μm, the addition rate of the doping ion solution is controlled to be 1-5L / h; preferably, the stirring speed is 100-1500r / min. Controlling the co-current dropwise addition operation conditions within the above range can make the obtained manganese iron phosphate lithium positive electrode material have better performance. Preferably, when the crystal size reaches 3-5μm, it also includes: continuously adding a surfactant to the co-precipitation crystallization reaction system until the co-precipitation crystallization reaction ends; preferably, the surfactant is vinylpyrrolidone; preferably, the addition rate of the surfactant is 0.2-0.5L / h; preferably, the surfactant is added in the form of an aqueous solution with a concentration of 0.1-1mol / L. Adding a surfactant to the co-precipitation crystallization reaction system can be more conducive to the formation of a gradient doping structure of the manganese iron phosphate precursor.
[0016] Furthermore, in step S3, when the particle size of the particles to be crystallized is 5 to 100 μm, the feeding is stopped and aging is performed; preferably, the particle size of the crystallized particles is 5 to 30 μm; preferably, the aging time is 4 to 8 hours. Controlling the crystallization conditions within the above range can make the obtained gradient-doped manganese iron phosphate precursor smaller and more uniform in particle size, and the performance of manganese iron phosphate lithium positive electrode material is better.
[0017] Further, the doped ion compound is one or more of nickel sulfate, nickel nitrate, cobalt nitrate, cobalt sulfate, magnesium nitrate, magnesium sulfate, magnesium acetate, tetrabutyl titanate, ammonium fluorotitanate, copper sulfate, ammonium polyvanadate, ammonium metavanadate, zirconium nitrate or chromium sulfate; preferably, the iron source is one or more of ferrous sulfate, ferrous oxalate, ferrous acetate and ferrous nitrate; preferably, the manganese source is one or more of manganous sulfate, manganous oxalate, manganous acetate and manganous nitrate; preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide and lithium dihydrogen phosphate; preferably, the complexing agent is one or more of ammonia water, ammonium oxalate, citric acid, malic acid, EDTA-2Na; preferably, the carbon source is one or more of polyethylene glycol, glucose, chitosan, PVP-K30 and CNT. The above compounds are selected when preparing lithium manganese iron phosphate positive electrode materials, and the effect is better.
[0018] Further, when adding the complexing agent in step S2, protective gas is first introduced into the reactor to adjust the pH to 3-6; preferably, the concentration of the complexing agent is 1.0-3.0 mol / L; preferably, the amount of the complexing agent added is 1-2 times the total molar amount of metal ions in the iron-manganese mixed solution and the doped ion solution; preferably, the concentration of phosphoric acid is 1.0-2.0 mol / L; preferably, the temperature of the coprecipitation crystallization reaction is 40-80°C; preferably, the washing solvent in step S4 is one or more of deionized water, ethanol, and acetone; preferably, the drying temperature is 100-500°C, and the drying time is 5-10h. The above conditions can make the obtained iron-manganese precursor have a higher purity.
[0019] Furthermore, the solid content of the mixed slurry is 30% to 40%. The above conditions can achieve better mixing effect and are beneficial to improving the comprehensive performance of the lithium manganese iron phosphate positive electrode material.
[0020] According to another aspect of the present invention, a lithium ion battery is provided, wherein the positive electrode plate of the lithium ion battery comprises the lithium iron manganese phosphate positive electrode material prepared above. The lithium ion battery has the advantages of high discharge gram capacity and high capacity retention rate, and the battery can effectively alleviate the manganese precipitation phenomenon during the cycle process.
[0021] The present invention provides a lithium iron manganese phosphate positive electrode material, which includes a doped manganese iron phosphate core and a coating layer coated on the surface of the doped manganese iron phosphate core, wherein the coating layer is a lithium-containing carbon layer; the doped manganese iron phosphate core includes doped ions, and the particles of the doped manganese iron phosphate core have a decreasing content gradient of manganese ions and iron ions from the inside to the outside, and an increasing content gradient of doped ions. The lithium iron manganese phosphate positive electrode material having the above structure can effectively improve the poor phase structure stability and poor conductivity of the lithium iron manganese phosphate positive electrode material, as well as a series of problems caused by the Jahn-Teller effect and manganese dissolution that may occur in the material itself, thereby improving the conductivity of the lithium iron manganese phosphate positive electrode material when used, and the comprehensive performance of various aspects such as gram capacity and cycle stability when used in batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0023] Figure 1 The Fe 0.38 Mn 0.6 Mg 0.02 SEM image of HPO4 precursor. DETAILED DESCRIPTION
[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0025] As described in the background technology section, compared with lithium iron phosphate positive electrode materials, lithium iron manganese phosphate positive electrode materials have a higher discharge platform, and their theoretical energy density can be increased by about 21% compared with lithium iron phosphate materials. However, due to the low phase structure stability of the material itself, the irregular micromorphology, the Jahn-Teller effect and manganese dissolution of the lithium iron manganese phosphate material itself, and the poor lithium ion conductivity of the lithium iron manganese phosphate material, the lithium iron manganese phosphate positive electrode material has the problem of rapid decay at the 4.1V voltage platform when used in the battery cycle process. The above factors further lead to the problems of poor cycle performance and severe capacity decay of the lithium iron manganese phosphate positive electrode material in the battery process.
[0026] In order to solve the above problems, the present invention provides a lithium iron manganese phosphate positive electrode material, which includes a doped manganese iron phosphate core and a coating layer coated on the surface of the doped manganese iron phosphate core, wherein the coating layer is a lithium-containing carbon layer; the doped manganese iron phosphate core includes doped ions, and the particles of the doped manganese iron phosphate core have a decreasing content gradient of manganese ions and iron ions from the inside to the outside, and an increasing content gradient of doped ions.
[0027] The lithium iron manganese phosphate positive electrode material of the present invention comprises two parts: a doped manganese iron phosphate core and a coating layer coated on the surface of the doped manganese iron phosphate core, wherein the coating layer is a lithium-containing carbon layer. The lithium iron manganese phosphate positive electrode material is a positive electrode material obtained by further doping manganese elements on the basis of lithium iron phosphate. The manganese in the conventional lithium iron manganese phosphate positive electrode material is often uniformly present in the lithium iron manganese phosphate material, which leads to the direct large-area contact of manganese with the electrolyte during the actual application process, which will lead to the dissolution of manganese, the deterioration of the material structure stability and the serious attenuation of the battery capacity. The present invention uses the doped manganese iron phosphate in the lithium iron manganese phosphate positive electrode material as the core of the material, and further coats it with a lithium-containing carbon coating layer. Due to the presence of the coating layer in the material, the manganese dissolution phenomenon existing in the lithium iron manganese phosphate material during use can be effectively improved, and the cyclicity and serious capacity attenuation of the lithium iron manganese phosphate positive electrode material can also be further improved. In addition, the coating layer of the lithium iron manganese phosphate positive electrode material described in the present invention is a lithium-containing carbon layer. Using lithium and carbon together as the coating layer of the doped manganese iron phosphate core can also further improve the conductivity of the lithium iron manganese phosphate positive electrode material and improve the comprehensive performance of the material.
[0028] In addition, in the doped iron manganese phosphate core of the lithium iron manganese phosphate positive electrode material described in the present application, from the inside to the outside, the content gradient of manganese ions and iron ions decreases, and the content gradient of doped ions increases. The doped iron manganese phosphate core of the lithium iron manganese phosphate positive electrode material described in the present invention adopts the above-mentioned more special structure, in which the content gradient of manganese ions and iron ions decreases from the inside to the outside, and the content gradient of doped ions increases from the inside to the outside. First, the gradient change of the element content can make the doped ions better embedded in the iron manganese phosphate core to form a solid solution, while not changing the electronic transmission performance of the iron manganese phosphate core, further exerting the conductivity of the doped ions in the lithium iron manganese phosphate positive electrode material, can effectively improve the conductivity and cycle stability of the lithium iron manganese phosphate positive electrode material, in addition, the doped ions and the iron manganese phosphate core exist in the form of a solid solution, which can make the material itself have a more stable phase structure. Secondly, the doping ions exist in the doped manganese iron phosphate core in the above-mentioned special gradient quantitative change mode, which can improve the interface conditions in the material, and then improve the Jahn-Teller effect in the material, which is obviously helpful for improving the cycle performance and stability of the material and optimizing the serious capacity attenuation of the battery. Further adding doping ions to the lithium manganese iron phosphate positive electrode material can also broaden the transmission channel of lithium ions and improve the overall conductivity of the material.
[0029] In summary, the lithium iron manganese phosphate positive electrode material provided by the present invention can effectively improve the poor phase structure stability, poor conductivity, manganese dissolution and a series of problems caused by the Jahn-Teller effect of the lithium iron manganese phosphate positive electrode material itself. In addition, the problems of poor cycle stability and severe capacity attenuation of the lithium iron manganese phosphate positive electrode material in the process of being used in batteries are further improved.
[0030] In a preferred embodiment, the chemical formula of lithium manganese iron phosphate positive electrode material is: LiFe 1-x-y Mn x M y PO4 / C, wherein 0.1≤x≤0.9, 0.002≤y≤0.02, and M is one or more of nickel, cobalt, magnesium, titanium, copper, vanadium, zirconium and chromium. The content and relative content of manganese, iron, lithium and doped metal in the lithium manganese iron phosphate positive electrode material will affect the overall performance of the material. According to the stoichiometric ratio of each component in the above chemical formula, the obtained lithium manganese iron phosphate positive electrode material has better comprehensive performance during use. Preferably, LiFe 1-x-y Mn x M yIn PO4 / C, 0.5≤x≤0.7, 0.01≤y≤0.02, the content ratio of each component is within the above range, and the comprehensive performance is better. Preferably, the carbon coating amount of the coating layer is 1% to 3%, and carbon and lithium are used as the main components in the coating layer, so that carbon and lithium and each component in the doped manganese iron phosphate core can work together to further improve the conductivity of the lithium manganese iron phosphate positive electrode material, improve the comprehensive performance of the material, and control the carbon coating amount within the above range. The material has a better effect. Preferably, the M is cobalt and / or magnesium, and the above two doped metal ions can make the obtained lithium manganese iron phosphate positive electrode material have better performance. Preferably, the particle size of the lithium manganese iron phosphate positive electrode material is 0.5μm to 10μm.
[0031] According to another aspect of the present invention, a method for preparing the above-mentioned lithium iron manganese phosphate positive electrode material is also provided, and the preparation method comprises the following steps: S1, dissolving a manganese source and an iron source in water to obtain a manganese-iron mixed solution; dissolving a soluble compound of doped ions in water to obtain a doped ion solution; S2, placing an aqueous solution of a complexing agent in a reaction vessel, and adding phosphoric acid to adjust the pH; S3, adding the manganese-iron mixed solution and the doped ion solution to the reaction vessel in a co-current dropwise manner to carry out a co-precipitation crystallization reaction to obtain a crystalline precipitate; during the co-current dropwise addition process, controlling the flow rate of the doped ion solution to gradually increase; S4, filtering, washing and drying the crystalline precipitate to obtain a gradient-doped iron manganese phosphate precursor; S5, mixing the iron manganese precursor with a lithium source, a carbon source and water to obtain a mixed slurry, and grinding, spray drying, sintering and crushing the mixed slurry to obtain a lithium iron manganese phosphate positive electrode material.
[0032] Specifically, the preparation method firstly dissolves a manganese source and an iron source in water to obtain a manganese-iron mixed solution; then dissolves a soluble compound of doped ions in water to obtain a doped ion solution, then places the complexing agent aqueous solution in a reaction container, and adjusts the pH with phosphoric acid; then adds the configured manganese-iron mixed solution and the doped ion solution to the reaction container in a co-current dropwise manner, so that the manganese-iron mixed solution and the doped ion solution undergo a co-precipitation crystallization reaction to obtain a crystalline precipitate, and the addition flow rate gradually increases when the doped ion solution is added, and then the obtained crystalline precipitate is filtered, washed and dried to obtain an iron-manganese precursor; finally, the iron-manganese precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, and the mixed slurry is subjected to sanding, spray drying, sintering and crushing to obtain a lithium iron manganese phosphate positive electrode material.
[0033] In the preparation process of the present invention, a manganese-iron mixed solution and a doping ion solution are first subjected to a coprecipitation crystallization reaction under the action of a complexing agent and phosphoric acid. The manganese-iron mixed solution and the doping ion solution are added to the reaction vessel in a cocurrent dropwise manner by controlling the addition of the manganese-iron mixed solution and the doping ion solution, and the addition flow rate is gradually increased when the doping ion solution is added during the cocurrent dropwise addition process, so as to obtain a crystalline precipitate with a reduced content gradient of manganese ions and iron ions and an increased content gradient of doping ions from the inside to the outside, and then a gradient-doped iron-manganese phosphate precursor can be obtained by further treatment. During the coprecipitation crystallization reaction, the manganese-iron mixed solution and the doping ion solution will affect the growth rate of the crystal surface of the crystalline precipitate due to the different types of metal ions and the changes in the content of metal ions in the system, thereby causing the formed crystalline precipitate to have a gradient-changing structure. Subsequently, the gradient-doped iron-manganese phosphate precursor is mixed with a lithium source, a carbon source and water and subjected to a series of treatments to obtain a manganese-iron phosphate lithium positive electrode material. The above-mentioned preparation method can make the prepared lithium manganese iron phosphate positive electrode material have a doped manganese iron phosphate core and a coating layer structure coated on the surface of the doped manganese iron phosphate core, and the particles of the doped manganese iron phosphate core have a decreasing content gradient of manganese ions and iron ions and an increasing content gradient of doped ions from the inside to the outside.
[0034] In fact, in the actual process of preparing the above-mentioned lithium manganese iron phosphate positive electrode material, due to the possible loss of lithium, etc., excessive lithium is often added during the preparation to obtain the material of the corresponding molecular formula. It is best to control the amount of lithium added to 1.02 to 1.08 times the sum of the molar amounts of Fe, Mn and Mg.
[0035] In a preferred embodiment, in step S1, the concentration of the ferromanganese mixed solution is 0.8-1.2 mol / L; preferably, the concentration of the doping ion solution is 0.3-0.6 mol / L. The concentration of the ferromanganese mixed solution and the concentration of the doping ion solution will affect the coprecipitation crystallization reaction. By controlling the concentration of the ferromanganese mixed solution and the concentration of the doping ion solution within the above range, the crystal size of the generated iron-manganese precursor can be effectively controlled within a smaller range, which is beneficial to the improvement of the comprehensive performance of the lithium iron manganese phosphate positive electrode material.
[0036] In a preferred embodiment, the co-current addition operation is carried out under stirring, and the addition rate of the manganese iron mixed solution is 0.5-5 L / h; preferably, the initial addition rate of the doping ion solution is 0.005-0.5 L / h, and when the crystal particle size reaches 3-5 μm, the addition rate of the doping ion solution is controlled to be 1-5 L / h. When the manganese iron mixed solution and the doping ion solution are subjected to a coprecipitation crystallization reaction under the action of a complexing agent and phosphoric acid, by controlling the addition rate of the doping ion solution within a variation range, the structure of the particles of the doped iron phosphate manganese core of the obtained manganese iron phosphate lithium positive electrode material can be made from the inside to the outside, the content gradient of manganese ions and iron ions decreases, and the content gradient of doping ions increases. Controlling the addition rate of the manganese iron mixed solution and the doping ion solution and the change of the addition rate within the above range can make the obtained manganese iron phosphate lithium positive electrode material have more excellent comprehensive performance. Preferably, when the crystal particle size reaches 3 to 5 μm, it also includes: continuously adding a surfactant to the coprecipitation crystallization reaction system until the coprecipitation crystallization reaction is completed; preferably, the surfactant is vinylpyrrolidone; preferably, the surfactant is added at a rate of 0.2 to 0.5 L / h; preferably, the surfactant is added in the form of an aqueous solution with a concentration of 0.1 to 1 mol / L. Adding a surfactant to the coprecipitation crystallization reaction system can further regulate the growth rate of the crystal surface of the crystalline precipitate by utilizing the difference in the adsorption rate of the surfactant on the crystal surface, which is more conducive to the formation of a gradient structure of the crystalline precipitate, so that the gradient doping structure generated by the iron manganese phosphate precursor is better. Preferably, the stirring speed during the addition is controlled to be 100 to 1500 r / min.
[0037] In a preferred embodiment, when the particle size of the particles to be crystallized in step S3 is 5 to 100 μm, the feeding is stopped and the aging is performed. The amount of manganese iron mixed solution and the doping ion solution added during the coprecipitation crystallization reaction will affect the particle size of the crystallized precipitate. The present invention controls the amount of reactants added in the above manner, so that the obtained iron manganese phosphate precursor has a good effect, and then the obtained manganese iron phosphate lithium positive electrode material has better performance. Preferably, the particle size of the crystalline particles is 5 to 30 μm, and the feeding is stopped when the particle size of the particles to be crystallized in step S3 is 5 to 30 μm. The above-mentioned method controls the amount of reactants added to make the obtained iron manganese phosphate precursor smaller and more uniform, and the corresponding obtained manganese iron phosphate lithium positive electrode material has better performance. Preferably, the aging time is 4 to 8 hours. Controlling the aging time within the above range can make the coprecipitation crystallization reaction more sufficient.
[0038] By way of example but not limitation, the doping ion compound is one or more of nickel sulfate, nickel nitrate, cobalt nitrate, cobalt sulfate, magnesium nitrate, magnesium acetate, tetrabutyl titanate, ammonium fluorotitanate, copper sulfate, ammonium polyvanadate, ammonium metavanadate, zirconium nitrate or chromium sulfate; preferably, the iron source is one or more of ferrous sulfate, ferrous oxalate, ferrous acetate and ferrous nitrate; preferably, the manganese source is one or more of manganous sulfate, manganous oxalate, manganous acetate and manganous nitrate; preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide and lithium dihydrogen phosphate; preferably, the complexing agent is one or more of ammonia water, ammonium oxalate, citric acid, malic acid, EDTA-2Na (disodium ethylenediaminetetraacetate); preferably, the carbon source is at least one of polyethylene glycol (PEG), glucose, chitosan, PVP-K30 (polyvinyl pyrrolidone-K30) and CNT (carbon nanotube). In theory, any compound that can realize the scheme of the present invention can be used, and the above compounds are preferably more effective.
[0039] In a preferred embodiment, when adding the complexing agent in step S2, a protective gas is first introduced into the reactor to adjust the pH to 3-6; preferably, the concentration of the complexing agent is 1.0-3.0 mol / L; preferably, the amount of the complexing agent added is 1-2 times the total molar amount of metal ions in the iron-manganese mixed solution and the doped ion solution; preferably, the concentration of phosphoric acid is 1.0-2.0 mol / L. When the coprecipitation crystallization reaction is carried out, the reaction conditions are controlled within the above range, so that the obtained lithium manganese iron phosphate positive electrode material has better cycle stability. Preferably, the temperature of the coprecipitation crystallization reaction is 40-80°C, and the above temperature is more conducive to the coprecipitation crystallization reaction. Preferably, the washing solvent in step S4 is one or more of deionized water, ethanol, and acetone; preferably, the drying temperature is 100-500°C, and the drying time is 5-10h. The above conditions can make the obtained iron-manganese precursor have a higher purity. Preferably, the protective gas is at least one of nitrogen or argon.
[0040] In a preferred embodiment, the solid content of the mixed slurry is 30% to 40%. When preparing the lithium manganese iron phosphate positive electrode material, controlling the solid content of the mixed slurry and controlling the grinding, spray drying and sintering conditions can make the obtained lithium manganese iron phosphate positive electrode material have better comprehensive performance.
[0041] According to another aspect of the present invention, a lithium-ion battery is provided, wherein the positive electrode plate of the lithium-ion battery comprises the lithium iron manganese phosphate positive electrode material prepared by the above preparation method.
[0042] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0043] Example 1
[0044] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.38 Mn 0.6 Mg 0.02 PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, when preparing the lithium manganese iron phosphate positive electrode material, the iron source is ferrous nitrate, the manganese source is manganous nitrate, the soluble compound of doped ions is magnesium sulfate, the lithium source is lithium carbonate, and the carbon source is a mixture of glucose and PEG in a mass ratio of 1:1. During preparation, the molar ratio of Fe, Mn and Mg in the manganese source, iron source and soluble compound of doped ions is 0.38:0.6:0.02, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe, Mn and Mg.
[0045] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0046] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; dissolving a soluble compound of a doping ion in water to obtain a 0.5 mol / L doping ion solution; placing water in a reaction kettle, adding citric acid to a concentration of 1 mol / L, wherein the molar amount of the citric acid is twice the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing nitrogen to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 3, and heating the reaction kettle to 55° C.
[0047] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.2L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ions is controlled to be 3L / h, and 1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.2L / h during the process; when the crystal particle size in the reactor is 8≤D50≤10μm, the dropwise addition is stopped, and aging is continued for 6h. The aged precipitate is filtered, washed with water, and dried at 300°C for 10h to obtain a gradient Mg-doped iron manganese phosphate precursor Fe 0.38 Mn 0.6 Mg 0.02 HPO4, and the precursor was tested by electron microscope. The SEM image obtained is as follows Figure 1 As shown in the figure, it can be seen that the gradient-doped manganese iron phosphate precursor prepared by the preparation method of the present invention presents a spherical agglomerate morphology and shows a high uniformity. In addition, no obvious broken balls are found. The above structural characteristics can further improve the overall conductivity of the material.
[0048] (3) The gradient Mg-doped iron manganese phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a lithium iron manganese phosphate positive electrode material LiFe with a carbon coating amount of 2%. 0.38 Mn 0.6 Mg 0.02 PO4 / C.
[0049] Example 2
[0050] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.39 Mn 0.6 Co 0.01 PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, when preparing the lithium manganese iron phosphate positive electrode material, the iron source is ferrous sulfate, the manganese source is manganous sulfate, the soluble compound of doped ions is cobalt sulfate, the lithium source is lithium carbonate, and the carbon source is glucose and PEG mixed in a mass ratio of 1:1. During preparation, the molar ratio of Fe, Mn and Co in the manganese source, iron source and soluble compound of doped ions is 0.39:0.6:0.01, and the molar amount of Li in the lithium source is 1.08 times the sum of the molar amounts of Fe, Mn and Co.
[0051] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0052] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; dissolving a soluble compound of a doping ion in water to obtain a 0.5 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 1 mol / L, wherein the molar amount of the ammonia water is twice the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing argon gas to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 6, and heating the reaction kettle to 55° C.
[0053] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.2L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ion is controlled to be 3L / h, and 0.1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.5L / h during the process; when the crystal particle size in the reactor is 8≤D50≤10μm, the dropwise addition is stopped, and aging is continued for 6h. The aged precipitate is filtered, washed with ethanol, and dried at 300°C for 10h to obtain a gradient Co-doped iron manganese phosphate precursor Fe 0.39 Mn 0.6 Co 0.01 HPO4.
[0054] (3) The gradient Co-doped manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron lithium phosphate positive electrode material LiFe with a carbon coating amount of 2%. 0.39 Mn 0.6 Co 0.01 PO4 / C.
[0055] Example 3
[0056] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.49 Mn 0.5 Co 0.01 PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, the ferrous sulfate used in the preparation of the lithium manganese iron phosphate positive electrode material, the manganese source is manganese sulfate, the soluble compound of doped ions is cobalt nitrate, the lithium source is lithium carbonate, and the carbon source is a mixture of glucose and PEG in a mass ratio of 1:1. During preparation, the molar ratio of Fe, Mn and Co in the manganese source, iron source and soluble compound of doped ions is 0.49:0.5:0.01, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe, Mn and Co.
[0057] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0058] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; dissolving a soluble compound of a doping ion in water to obtain a 0.5 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 1 mol / L, wherein the molar amount of the ammonia water is twice the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing argon gas to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 6, and heating the reaction kettle to 55° C.
[0059] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.2L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ion is controlled to be 3L / h, and 0.1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.5L / h during the process; when the crystal particle size in the reactor is 8≤D50≤10μm, the dropwise addition is stopped, and aging is continued for 6h. The aged precipitate is filtered, washed with ethanol, and dried at 300°C for 10h to obtain a gradient Co-doped iron manganese phosphate precursor Fe 0.49 Mn 0.5 Co 0.01 HPO4.
[0060] (3) The gradient Co-doped manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron lithium phosphate positive electrode material LiFe with a carbon coating amount of 2%. 0.49 Mn 0.5 Co 0.01 PO4 / C.
[0061] Example 4
[0062] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.28 Mn 0.7 Mg 0.02PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, the ferrous sulfate used in the preparation of the manganese iron phosphate lithium positive electrode material, the manganese source is manganese sulfate, the soluble compound of doped ions is magnesium acetate, the lithium source is lithium carbonate, and the carbon source is a mixture of glucose and PEG in a mass ratio of 1:1. During preparation, the molar ratio of Fe, Mn and Mg in the manganese source, iron source and soluble compound of doped ions is 0.28:0.7:0.02, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe, Mn and Mg.
[0063] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0064] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; dissolving a soluble compound of a doping ion in water to obtain a 0.5 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 1 mol / L, wherein the molar amount of the ammonia water is 1.5 times the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing argon gas to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 6, and heating the reaction kettle to 55° C.
[0065] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.2L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ion is controlled to be 3L / h, and 0.1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.5L / h during the process; when the crystal particle size in the reactor is 8≤D50≤10μm, the dropwise addition is stopped, and aging is continued for 6h. The aged precipitate is filtered, washed with ethanol, and dried at 300°C for 10h to obtain a gradient Mg-doped iron manganese phosphate precursor Fe 0.49 Mn 0.5 Mg 0.01 HPO4.
[0066] (3) The gradient Mg-doped iron manganese phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a lithium iron manganese phosphate positive electrode material LiFe with a carbon coating amount of 2%. 0.28 Mn 0.7 Mg 0.02 PO4 / C.
[0067] Example 5
[0068] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.898 Mn 0.1 Co 0.002 PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, the ferrous sulfate used in the preparation of the manganese iron phosphate lithium positive electrode material, the manganese source is manganese sulfate, the soluble compound of doped ions is cobalt nitrate, the lithium source is lithium carbonate, and the carbon source is glucose. During preparation, the molar ratio of Fe, Mn and Co in the manganese source, iron source and soluble compound of doped ions is 0.898:0.1:0.002, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe, Mn and Co.
[0069] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0070] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; dissolving a soluble compound of doping ions in water to obtain a 0.5 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 1 mol / L, wherein the molar amount of the ammonia water is 1 times the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing argon gas to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 6, and heating the reaction kettle to 55° C.
[0071] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.2L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ion is controlled to be 3L / h, and 0.1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.5L / h during the process; when the crystal particle size in the reactor is 8≤D50≤10μm, the dropwise addition is stopped, and aging is continued for 6h. The aged precipitate is filtered, washed with ethanol, and dried at 300°C for 10h to obtain a gradient Co-doped iron manganese phosphate precursor Fe 0.898 Mn 0.1 Co 0.002 HPO4.
[0072] (3) The gradient Co-doped manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron phosphate lithium positive electrode material LiFe0.898 Mn 0.1 Co 0.002 PO4 / C.
[0073] Example 6
[0074] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.08 Mn 0.9 Mg 0.02 PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, the ferrous sulfate used in preparing the lithium manganese iron phosphate positive electrode material, the manganese source is manganese sulfate, the soluble compound of doped ions is magnesium nitrate, the lithium source is lithium carbonate, and the carbon source is glucose. During preparation, the molar ratio of Fe, Mn and Mg in the manganese source, iron source and soluble compound of doped ions is 0.08:0.9:0.02, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe, Mn and Mg.
[0075] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0076] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; dissolving a soluble compound of a doping ion in water to obtain a 0.5 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 1 mol / L, wherein the molar amount of the ammonia water is twice the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing argon gas to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 6, and heating the reaction kettle to 55° C.
[0077] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.2L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ion is controlled to be 3L / h, and 0.1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.5L / h during the process; when the crystal particle size in the reactor is 8≤D50≤10μm, the dropwise addition is stopped, and aging is continued for 6h. The aged precipitate is filtered, washed with ethanol, and dried at 300°C for 10h to obtain a gradient Mg-doped iron manganese phosphate precursor Fe 0.08 Mn 0.9 Mg 0.02 HPO4.
[0078] (3) The gradient Mg-doped iron manganese phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a lithium iron manganese phosphate positive electrode material LiFe with a carbon coating amount of 2%. 0.88 Mn 0.1 Mg 0.02 PO4 / C.
[0079] Example 7
[0080] The difference between Example 7 and Example 2 is that the speed of the co-current dripping process is different.
[0081] A lithium manganese iron phosphate positive electrode material has the molecular formula: Li Fe 0.39 Mn 0.6 Co 0.01 PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, when preparing the lithium manganese iron phosphate positive electrode material, the iron source is ferrous sulfate, the manganese source is manganous sulfate, the soluble compound of doped ions is cobalt sulfate, the lithium source is lithium carbonate, and the carbon source is a mixture of glucose and PEG in a mass ratio of 1:1. During preparation, the molar ratio of Fe, Mn and Co in the manganese source, iron source and soluble compound of doped ions is 0.39:0.6:0.01, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe, Mn and Co.
[0082] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0083] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; dissolving a soluble compound of a doping ion in water to obtain a 0.5 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 1 mol / L, wherein the molar amount of the ammonia water is twice the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing argon gas to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 6, and heating the reaction kettle to 55° C.
[0084] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 0.5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.005L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ion is controlled to be 1L / h, and 0.1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.5L / h during the process; when the crystal particle size in the reactor is 8≤D50≤10μm, the dropwise addition is stopped, and aging is continued for 6h. The aged precipitate is filtered, washed with ethanol, and dried at 300°C for 10h to obtain a gradient Co-doped iron manganese phosphate precursor Fe 0.39 Mn 0.6 Co 0.01 HPO4.
[0085] (3) The gradient Co-doped manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron lithium phosphate positive electrode material LiFe with a carbon coating amount of 2%. 0.39 Mn 0.6 Co 0.01 PO4 / C.
[0086] Example 8
[0087] The difference between Example 8 and Example 2 is that the speed of the co-current dripping process is different.
[0088] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.39 Mn 0.6 Co 0.01 PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, when preparing the lithium manganese iron phosphate positive electrode material, the iron source is ferrous sulfate, the manganese source is manganous sulfate, the soluble compound of doped ions is cobalt sulfate, the lithium source is lithium carbonate, and the carbon source is a mixture of glucose and PEG in a mass ratio of 1:1. During preparation, the molar ratio of Fe, Mn and Co in the manganese source, iron source and soluble compound of doped ions is 0.39:0.6:0.01, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe, Mn and Co.
[0089] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0090] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; dissolving a soluble compound of a doping ion in water to obtain a 0.5 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 1 mol / L, wherein the molar amount of the ammonia water is twice the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing argon gas to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 6, and heating the reaction kettle to 55° C.
[0091] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.5L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ion is controlled to be 5L / h, and 0.1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.5L / h during the process; when the crystal particle size in the reactor is 8≤D50≤10μm, the dropwise addition is stopped, and aging is continued for 6h. The aged precipitate is filtered, washed with ethanol, and dried at 300°C for 10h to obtain a gradient Co-doped iron manganese phosphate precursor Fe 0.39 Mn 0.6 Co 0.01 HPO4.
[0092] (3) The gradient Co-doped manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron lithium phosphate positive electrode material LiFe with a carbon coating amount of 2%. 0.39 Mn 0.6 Co 0.01 PO4 / C.
[0093] Example 9
[0094] The difference between Example 9 and Example 2 is that the feeding is stopped when the particle size of the crystal particles is 30 to 100 μm.
[0095] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.39 Mn 0.6 Co 0.01PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, when preparing the lithium manganese iron phosphate positive electrode material, the iron source is ferrous sulfate, the manganese source is manganous sulfate, the soluble compound of doped ions is cobalt sulfate, the lithium source is lithium carbonate, and the carbon source is a mixture of glucose and PEG in a mass ratio of 1:1. During preparation, the molar ratio of Fe, Mn and Co in the manganese source, iron source and soluble compound of doped ions is 0.39:0.6:0.01, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe, Mn and Co.
[0096] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0097] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; dissolving a soluble compound of a doping ion in water to obtain a 0.5 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 1 mol / L, wherein the molar amount of the ammonia water is twice the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing argon gas to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 6, and heating the reaction kettle to 55° C.
[0098] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.2L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ion is controlled to be 3L / h, and 0.1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.5L / h during the process; when the crystal particle size in the reactor is 30≤D50≤100μm, the dropwise addition is stopped, and aging is continued for 6h. The aged precipitate is filtered, washed with ethanol, and dried at 300°C for 10h to obtain a gradient Co-doped iron manganese phosphate precursor Fe 0.39 Mn 0.6 Co 0.01 HPO4.
[0099] (3) The gradient Co-doped manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron phosphate lithium positive electrode material LiFe 0.39 Mn 0.6 Co 0.01 PO4 / C.
[0100] Example 10
[0101] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.39 Mn 0.6 V 0.01 PO4 / C, with a carbon coating amount of 1% and a particle size of 0.5μm≤D50≤2μm. Among them, when preparing the lithium manganese iron phosphate positive electrode material, the iron source is ferrous sulfate, the manganese source is manganous sulfate, the soluble compound of doped ions is a 1:1 composite of ammonium polyvanadate and ammonium metavanadate in a molar ratio, the lithium source is lithium carbonate, and the carbon source is PEG. During preparation, the molar ratio of Fe, Mn and V in the manganese source, iron source and soluble compound of doped ions is 0.39:0.6:0.01, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe, Mn and V.
[0102] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0103] (1) dissolving a manganese source and an iron source in water to obtain a 0.8 mol / L manganese-iron mixed solution; dissolving a soluble compound of doping ions in water to obtain a 0.6 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 3 mol / L, wherein the molar amount of the ammonia water is 1 times the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing nitrogen gas to place the reaction kettle in a protective gas range, then adding 1 mol / L phosphoric acid to adjust the pH to 3, and heating the reaction kettle to 40°C.
[0104] (2) When the stirring speed of the reactor is 100r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.2L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ions is controlled to be 3L / h, and 0.1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.5L / h during the process; when the crystal particle size in the reactor is 8≤D50≤10μm, the dropwise addition is stopped, and aging is continued for 4h. The aged precipitate is filtered, washed with acetone, and dried at 100°C for 10h to obtain a gradient V-doped iron manganese phosphate precursor Fe 0.39 Mn 0.6 V 0.01 HPO4.
[0105] (3) The gradient V-doped manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 30%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron lithium phosphate positive electrode material LiFe with a carbon coating amount of 1%. 0.39 Mn 0.6 V 0.01 PO4 / C.
[0106] Embodiment 11
[0107] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.39 Mn 0.6 Zr 0.01 PO4 / C, with a carbon coating amount of 3% and a particle size of 0.5μm≤D50≤2μm. Among them, when preparing the lithium manganese iron phosphate positive electrode material, the iron source is ferrous sulfate, the manganese source is manganous sulfate, the soluble compound of doped ions is zirconium nitrate, the lithium source is lithium carbonate, and the carbon source is glucose. During preparation, the molar ratio of Fe, Mn and Zr in the manganese source, iron source and soluble compound of doped ions is 0.39:0.6:0.01, and the molar amount of Li in the lithium source is 1.08 times the sum of the molar amounts of Fe, Mn and Zr.
[0108] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0109] (1) dissolving a manganese source and an iron source in water to obtain a 1.2 mol / L manganese-iron mixed solution; dissolving a soluble compound of a doping ion in water to obtain a 0.3 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 1 mol / L, wherein the molar amount of the ammonia water is 1 times the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing argon gas to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 6, and heating the reaction kettle to 80°C.
[0110] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.2L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ion is controlled to be 3L / h, and 0.1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.5L / h during the process; when the crystal particle size in the reactor is 8≤D50≤10μm, the dropwise addition is stopped, and aging is continued for 8h. The aged precipitate is filtered, washed with water, and dried at 500°C for 5h to obtain a gradient Zr-doped iron manganese phosphate precursor Fe0.39 Mn 0.6 Zr 0.01 HPO4.
[0111] (3) The gradient Zr-doped manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 40%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron lithium phosphate positive electrode material LiFe with a carbon coating amount of 3%. 0.39 Mn 0.6 Zr 0.01 PO4 / C.
[0112] Example 12
[0113] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.39 Mn 0.6 Co 0.01 PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, when preparing the lithium manganese iron phosphate positive electrode material, the iron source is ferrous sulfate, the manganese source is manganous sulfate, the soluble compound of doped ions is cobalt sulfate, the lithium source is lithium carbonate, and the carbon source is a mixture of glucose and PEG in a mass ratio of 1:1. During preparation, the molar ratio of Fe, Mn and Co in the manganese source, iron source and soluble compound of doped ions is 0.39:0.6:0.01, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe, Mn and Co.
[0114] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0115] (1) dissolving a manganese source and an iron source in water to obtain a 1.5 mol / L manganese-iron mixed solution; dissolving a soluble compound of a doping ion in water to obtain a 1 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 1 mol / L, wherein the molar amount of the ammonia water is twice the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing argon gas to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 7, and heating the reaction kettle to 55° C.
[0116] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are added to the reactor in a parallel flow dropwise manner to carry out a co-precipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the initial addition rate of the doping ion solution is controlled to be 0.2L / h. When the crystal particle size reaches 3-5μm, the addition rate of the doping ion is controlled to be 3L / h, and 0.1mol / L of vinylpyrrolidone aqueous solution is added at a rate of 0.5L / h during the process; when the crystal particle size in the reactor is 100≤D50≤150μm, the dropwise addition is stopped, and aging is continued for 2h. The aged precipitate is filtered, washed with ethanol, and dried at 100°C for 5h to obtain a gradient Co-doped iron manganese phosphate precursor Fe 0.39 Mn 0.6 Co 0.01 HPO4.
[0117] (3) The gradient Co-doped manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron lithium phosphate positive electrode material LiFe with a carbon coating amount of 2%. 0.39 Mn 0.6 Co 0.01 PO4 / C.
[0118] Comparative Example 1
[0119] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.4 Mn 0.6 PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, the iron source for preparing the lithium manganese iron phosphate positive electrode material is ferrous nitrate, the manganese source is manganous nitrate, the lithium source is lithium carbonate, and the carbon source is glucose. During preparation, the molar ratio of Fe and Mn in the manganese source and the iron source is 0.4:0.6, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe and Mn.
[0120] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0121] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; placing water in a reaction kettle, adding citric acid to make the concentration 1 mol / L, wherein the molar amount of the citric acid is twice the total molar amount of metal ions in the iron-manganese mixed solution, at the same time, starting the stirring of the reaction kettle and introducing nitrogen to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 3, and heating the reaction kettle to 55° C.
[0122] (2) When the stirring speed of the reactor is 1500 r / min, the manganese iron mixed solution is added to the reactor for coprecipitation crystallization reaction. When the crystal particle size in the reactor is 8≤D50≤10 μm, the reaction is stopped and the aging is continued for 6 hours. The aged precipitate is filtered, washed with water, and dried at 60° C. for 10 hours to obtain the iron manganese phosphate precursor Fe 0.4 Mn 0.6 HPO4.
[0123] (3) The above-mentioned manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron phosphate lithium positive electrode material LiFe with a carbon coating amount of 2%. 0.4 Mn 0.6 PO4 / C.
[0124] Comparative Example 2
[0125] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.40 Mn 0.6 PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, the iron source for preparing the lithium manganese iron phosphate positive electrode material is ferrous nitrate, the manganese source is manganous nitrate, the lithium source is lithium carbonate, and the carbon source is a mixture of glucose and PEG in a mass ratio of 1:1. During preparation, the molar ratio of Fe and Mn in the manganese source and the iron source is 0.40:0.6, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe and Mn.
[0126] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0127] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; placing water in a reaction kettle, adding citric acid to make the concentration 1 mol / L, wherein the molar amount of the citric acid is twice the total molar amount of metal ions in the iron-manganese mixed solution, at the same time, starting the stirring of the reaction kettle and introducing nitrogen to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 3, and heating the reaction kettle to 55° C.
[0128] (2) When the stirring speed of the reactor is 1500r / min, the above-mentioned manganese iron mixed solution is added to the reactor in a dropwise manner to carry out a coprecipitation crystallization reaction, wherein the addition rate of the manganese iron mixed solution is controlled to be 5L / h, and the addition rate of 0.1mol / L vinyl pyrrolidone is controlled to be 0.5L / h. When the crystal particle size in the reactor is 8≤D50≤10μm, the dropwise addition is stopped, and the aging is continued for 6h. The aged precipitate is filtered, washed with water, and dried at 300°C for 10h to obtain a gradient iron manganese phosphate precursor Fe 0.4 Mn 0.6 HPO4.
[0129] (3) The gradient manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron phosphate lithium positive electrode material LiFe with a carbon coating amount of 2%. 0.4 Mn 0.6 PO4 / C.
[0130] Comparative Example 3
[0131] A molecular formula of lithium manganese iron phosphate positive electrode material is: LiFe 0.39 Mn 0.6 Co 0.01 PO4 / C, with a carbon coating amount of 2% and a particle size of 0.5μm≤D50≤2μm. Among them, when preparing the lithium manganese iron phosphate positive electrode material, the iron source is ferrous sulfate, the manganese source is manganous sulfate, the soluble compound of doped ions is cobalt sulfate, the lithium source is lithium carbonate, and the carbon source is glucose and PEG mixed in a mass ratio of 1:1. During preparation, the molar ratio of Fe, Mn and Co in the manganese source, iron source and soluble compound of doped ions is 0.39:0.6:0.01, and the molar amount of Li in the lithium source is 1.02 times the sum of the molar amounts of Fe, Mn and Co.
[0132] The preparation method of the above-mentioned lithium manganese iron phosphate positive electrode material is:
[0133] (1) dissolving a manganese source and an iron source in water to obtain a 1 mol / L manganese-iron mixed solution; dissolving a soluble compound of a doping ion in water to obtain a 0.5 mol / L doping ion solution; placing water in a reaction kettle, adding ammonia water to make the concentration 1 mol / L, wherein the molar amount of the ammonia water is twice the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution, at the same time, starting the stirring of the reaction kettle and introducing argon gas to place the reaction kettle in a protective gas range, then adding 2 mol / L phosphoric acid to adjust the pH to 6, and heating the reaction kettle to 55° C.
[0134] (2) When the stirring speed of the reactor is 1500 r / min, the above-mentioned manganese iron mixed solution and the above-mentioned doping ion solution are mixed in the ratio of elements described in the molecular formula and added into the reactor; when the crystal particle size in the reactor is 8≤D50≤10μm, the reaction is stopped and the aging is continued for 6h. The aged precipitate is filtered, washed with ethanol, and dried at 300°C for 10h to obtain Co-doped iron manganese phosphate precursor Fe 0.39 Mn 0.6 Co 0.01 HPO4.
[0135] (3) The Co-doped manganese iron phosphate precursor is mixed with a lithium source, a carbon source and water to obtain a mixed slurry, wherein the solid content of the mixed slurry is 35%, and the mixed slurry is subjected to grinding, spray drying, sintering and air flow pulverization to obtain a manganese iron lithium phosphate positive electrode material LiFe with a carbon coating amount of 2%. 0.39 Mn 0.6 Co 0.01 PO4 / C.
[0136] The lithium iron manganese phosphate positive electrode materials prepared in Examples 1 to 12 and Comparative Examples 1 to 3 were tested for relevant performances, and used in lithium ion batteries to test their relevant performances, wherein the preparation methods of the battery positive electrode and the preparation methods of the lithium ion battery and the relevant test methods are described as follows:
[0137] Notes on the preparation of battery positive electrode and lithium-ion battery:
[0138] (1) Preparation of slurry: 23.75 g of positive electrode material, 0.5 g of superconducting carbon black (SP) and 0.75 g of binder polyvinylidene fluoride (PVDF) were added into a 500 mL agate ball mill, and 16 g of N-methylpyrrolidone (NMP) was added as a solvent. The mixture was ball milled at a speed of 360 r / min for 4 h to prepare a slurry.
[0139] (2) Preparation of positive electrode: Adjust the scale of the scraper of the coating machine, evenly apply the slurry prepared above on the aluminum foil, place the coated electrode in a vacuum drying oven, and bake at 130°C for 3 hours; place the aluminum foil coated with the slurry flatly in the middle of the roller, and roll the electrode; place the front of the rolled electrode close to the punched area, and punch the electrode in sequence; the compaction density of the electrode is controlled at 2.0-2.4 g / cm 3 , with a diameter of 14 mm and a thickness of 0.05 to 0.10 mm; the punched electrode piece is placed in a vacuum drying oven at a temperature of 130°C and baked for 3 hours to obtain a positive electrode piece;
[0140] (3) Assembly of button cells: In a glove box, the negative electrode shell, spring sheet, steel sheet, lithium sheet, separator, positive electrode sheet and positive electrode shell are assembled in sequence. During the process, 10 μL of 1 mol / L LiPF6 electrolyte is injected, wherein the electrolyte contains a 1:1 volume ratio of ethylene carbonate (EC) / diethyl carbonate (DEC) mixed solution as a solvent. The button cell is then sealed with a sealing machine to obtain a button cell.
[0141] Notes on the test method:
[0142] Powder resistivity test: The powder resistivity was tested by a four-probe method. 0.4 g of lithium manganese iron phosphate positive electrode material powder was taken and its resistivity was tested at a pressure of 30 MPa for 10 seconds. The results are shown in Table 1.
[0143] The test method of manganese dissolution after 500 cycles: After 500 cycles, take the negative electrode and dry it, scrape 5g of powder with a blade, dissolve it in 200mL of 0.008mol / L hydrochloric acid solution, stir at 880rpm for 30min, place it in a 25℃ constant temperature water bath for 2h after stirring, then filter the above solution, take 1ml of the filtrate and place it in a 50ml volumetric flask, add 2mLGR concentrated nitric acid, dilute to the scale, and perform ICP detection. The specific situation of manganese dissolution of the positive electrode prepared by the present invention can be reflected according to the manganese content in the negative electrode.
[0144] The lithium iron manganese phosphate positive electrode materials prepared in Examples 1 to 13 and Comparative Examples 1 to 3 were subjected to powder resistivity test according to the above method. The lithium iron manganese phosphate positive electrode materials prepared in the above Examples and Comparative Examples were respectively prepared into corresponding button batteries according to the above method for preparing button batteries, and the 0.2C discharge capacity, 1C discharge capacity, and 1C capacity retention rate after 500 cycles of charge and discharge were tested respectively, and the Mn dissolution amount after 500 cycles was tested.
[0145] The performance test results of lithium manganese iron phosphate positive electrode materials and the relevant performance test results of lithium ion batteries when using them in lithium ion batteries are shown in Table 1.
[0146] Table 1
[0147]
[0148]
[0149] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: the gradient-doped lithium iron manganese phosphate positive electrode material prepared in the embodiments of the present application has a lower resistivity, and when it is applied to a battery, it exhibits a better gram capacity performance. In addition, the lithium iron manganese phosphate positive electrode material prepared in the embodiments of the present invention has less manganese dissolution when applied to a battery, indicating that the material structure proposed in the present invention can effectively improve defects such as the Jahn-Teller effect and manganese dissolution, thereby making the battery exhibit better conductivity and cycle stability. The preparation process parameters are controlled within the preferred range, and the comprehensive performance of the obtained lithium iron manganese phosphate positive electrode material is better. In contrast, in Comparative Examples 1 to 3, the prepared lithium iron manganese phosphate positive electrode materials are either undoped with metal ions or are not the gradient structure proposed in the present invention, and their comprehensive performance is far from the structure proposed in the present invention.
[0150] In summary, the gradient-doped lithium iron manganese phosphate positive electrode material proposed in the present invention can effectively improve the poor phase structure stability, poor lithium ion conductivity, Jahn-Teller effect and manganese dissolution of the lithium iron manganese phosphate positive electrode material, and other problems, thereby improving the comprehensive performance of the lithium iron manganese phosphate positive electrode material in terms of conductivity and cycle stability during application.
[0151] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium manganese iron phosphate positive electrode material, characterized in that: The lithium iron manganese phosphate positive electrode material includes a doped manganese iron phosphate core and a coating layer coated on the surface of the doped manganese iron phosphate core, wherein the coating layer is a lithium-containing carbon layer; the doped manganese iron phosphate core includes doped ions, and from the inside to the outside of the particles of the doped manganese iron phosphate core, the content gradient of manganese ions and iron ions decreases, and the content gradient of the doped ions increases.
2. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The chemical formula of the lithium manganese iron phosphate positive electrode material is: LiFe 1-x-y Mn x M y PO4 / C, wherein 0.1≤x≤0.9, 0.002≤y≤0.02, and M is one or more of nickel, cobalt, magnesium, titanium, copper, vanadium, zirconium and chromium; Preferably, the LiFe 1-x-y Mn x M y In PO4 / C, 0.5≤x≤0.7, 0.01≤y≤0.02; Preferably, the particle size of the lithium manganese iron phosphate positive electrode material is 0.5 to 10 μm; Preferably, the carbon coating amount of the coating layer is 1% to 3%; Preferably, M is cobalt and / or magnesium.
3. A method for preparing the lithium manganese iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1, dissolving a manganese source and an iron source in water to obtain a manganese-iron mixed solution; dissolving a soluble compound of doping ions in water to obtain a doping ion solution; S2, placing the complexing agent aqueous solution in a reaction vessel, and adding phosphoric acid to adjust the pH; S3, adding the manganese iron mixed solution and the doping ion solution into the reaction container in a co-current dripping manner to perform a co-precipitation crystallization reaction to obtain a crystalline precipitate; during the co-current dripping process, controlling the flow rate of the doping ion solution to gradually increase; S4, filtering, washing and drying the crystalline precipitate to obtain a gradient-doped iron manganese phosphate precursor; S5, mixing the iron-manganese precursor with a lithium source, a carbon source and water to obtain a mixed slurry, and grinding, spray-drying, sintering and crushing the mixed slurry to obtain the lithium iron manganese phosphate positive electrode material.
4. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 3, characterized in that: In step S1, the concentration of the ferromanganese mixed solution is 0.8-1.2 mol / L; Preferably, the concentration of the doping ion solution is 0.3-0.6 mol / L.
5. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 4, characterized in that: The co-current dropwise addition operation is performed under stirring, and the addition rate of the ferromanganese mixed solution is 0.5 to 5 L / h; Preferably, the initial addition rate of the doping ion solution is 0.005 to 0.5 L / h, and when the crystal particle size reaches 3 to 5 μm, the addition rate of the doping ion solution is controlled to be 1 to 5 L / h; Preferably, when the crystal particle size reaches 3-5 μm, the method further comprises: continuously adding a surfactant to the coprecipitation crystallization reaction system until the coprecipitation crystallization reaction is completed; Preferably, the surfactant is vinylpyrrolidone; Preferably, the surfactant is added at a rate of 0.2 to 0.5 L / h; Preferably, the surfactant is added in the form of an aqueous solution with a concentration of 0.1 to 1 mol / L; Preferably, the stirring speed is 100-1500 r / min.
6. The method for preparing the lithium iron manganese phosphate positive electrode material according to any one of claims 3 to 5, characterized in that: In the step S3, when the particle size of the crystal particles is 5 to 100 μm, the feeding is stopped and aging is performed; Preferably, the particle size of the crystalline particles is 5 to 30 μm; Preferably, the aging time is 4 to 8 hours.
7. The method for preparing the lithium iron manganese phosphate positive electrode material according to any one of claims 3 to 5, characterized in that: The doping ion compound is one or more of nickel sulfate, nickel nitrate, cobalt nitrate, cobalt sulfate, magnesium nitrate, magnesium sulfate, magnesium acetate, tetrabutyl titanate, ammonium fluorotitanate, copper sulfate, ammonium polyvanadate, ammonium metavanadate, zirconium nitrate or chromium sulfate; Preferably, the iron source is one or more of ferrous sulfate, ferrous oxalate, ferrous acetate and ferrous nitrate; Preferably, the manganese source is one or more of manganous sulfate, manganous oxalate, manganous acetate and manganous nitrate; Preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide and lithium dihydrogen phosphate; Preferably, the complexing agent is one or more of ammonia water, ammonium oxalate, citric acid, malic acid, and EDTA-2Na; Preferably, the carbon source is one or more of polyethylene glycol, glucose, chitosan, PVP-K30 and CNT.
8. The method for preparing the lithium iron manganese phosphate positive electrode material according to any one of claims 3 to 5, characterized in that: When adding the complexing agent in step S2, firstly introduce protective gas into the reactor to adjust the pH to 3-6; Preferably, the concentration of the complexing agent is 1.0 to 3.0 mol / L; Preferably, the added amount of the complexing agent is 1 to 2 times the total molar amount of metal ions in the iron-manganese mixed solution and the doping ion solution; Preferably, the concentration of the phosphoric acid is 1.0 to 2.0 mol / L; Preferably, the temperature of the coprecipitation crystallization reaction is 40 to 80°C; Preferably, the washing solvent in step S4 is one or more of deionized water, ethanol, and acetone; Preferably, the drying temperature is 100-500° C., and the drying time is 5-10 hours.
9. The method for preparing the lithium iron manganese phosphate positive electrode material according to any one of claims 3 to 5, characterized in that: The solid content of the mixed slurry is 30% to 40%.
10. A lithium ion battery, characterized in that: The positive electrode plate of the lithium-ion battery comprises the lithium iron manganese phosphate positive electrode material prepared by the method for preparing the lithium iron manganese phosphate positive electrode material according to any one of claims 3 to 9.
Citation Information
Patent Citations
Hydrothermal synthesis method for lithium ferromanganese phosphate anode material of lithium ion battery
CN102249208A
Preparation method of lithium iron manganese phosphate cathode composite material
CN102738465A
Modified lithium ferric manganese phosphate anode material and preparation method thereof
CN102969506A
Preparation method for carbon compounded lithium ferromanganese phosphate used for lithium ion battery
CN103000898A
Method for preparing ferromanganese phosphate through coprecipitation and application thereof
CN115321507A
Cited By
Gradient doping type lithium iron manganese phosphate positive electrode material as well as preparation method and application thereof
CN120809776A
Gradient-doped lithium manganese iron phosphate positive electrode material, preparation method and application thereof
CN120809776B
Lithium manganese iron phosphate positive electrode material, preparation method thereof and lithium ion battery
CN120955111A
Vanadium manganese sodium phosphate positive electrode material and preparation method and application thereof
CN120964754A
Lithium manganese iron phosphate positive electrode material, preparation method and pure power battery
CN121331804A